2022
DOI: 10.1002/stc.3086
|View full text |Cite
|
Sign up to set email alerts
|

Optimum design of a tuned‐mass damper with negative stiffness device subjected to ground excitation

Abstract: In this study, a negative stiffness device based on the magnetic principle is presented and experimentally tested. Then, a tuned mass damper with a negative stiffness device (denoted as TMD_NSD) subjected to harmonic support excitation is optimized in terms of H ∞ optimization criterion, H2 optimization criterion, and stability maximization criterion (SMC). Closed-form expressions for the optimal tuning parameters are derived in terms of both H ∞ criterion and SMC, while the optimal tuning parameters are numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…As for the research on vibration reduction, experiments and analytical models have been carried out to investigate the dynamic response control under harmonic and earthquake excitations, and the results indicated that the vibration-reducing effects of a bistable attachment [29] and a bistable tuned-mass damper (BTMD) [30] were effective for a bistable oscillator and a bridge deck, respectively. In addition, bistable vibration isolation (BVI) [31,32] and quasi-zero stiffness (QZS) [33] isolation devices have been developed, and experiments have shown that these devices can significantly improve the vibration isolation effect through the snap-through effect of the bistable structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the research on vibration reduction, experiments and analytical models have been carried out to investigate the dynamic response control under harmonic and earthquake excitations, and the results indicated that the vibration-reducing effects of a bistable attachment [29] and a bistable tuned-mass damper (BTMD) [30] were effective for a bistable oscillator and a bridge deck, respectively. In addition, bistable vibration isolation (BVI) [31,32] and quasi-zero stiffness (QZS) [33] isolation devices have been developed, and experiments have shown that these devices can significantly improve the vibration isolation effect through the snap-through effect of the bistable structures.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [37] and Ullslam et al [38] proposed an innovative dynamic vibration absorber (DVA) and a vibration isolator using negative stiffness and focused on examining the optimal frequency ratio and negative stiffness ratio using the fixed-point theory. Zhang et al [33] invented a tuned-mass damper with a negative stiffness device (TMD_NSD) and verified its excellent vibration-suppressing effect by experimental tests. Charef et al [39] studied a non-traditional tuned-mass damper (NTTMD) employing negative stiffness to dampen a primary system, achieving better optimal tuning parameters.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the limitations of the common DVAs in vibration reduction of primary structure, researchers have explored other solutions, such as the introduction of negative stiffness devices, [18][19][20] flywheel inertial with lever fixed at ground, 21 and lever mechanism. 22 inspired by.…”
Section: Introductionmentioning
confidence: 99%